Using Digital Literacy in Conservation Efforts - Khoirunnisa, Aulia Wahyu; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The transition from mechanical and analog technology to digital technology is a defining characteristic of the digital era. The advent of technology has prompted the millennial generation to comprehend the significance of cultural preservation, encompassing their cognitive processes and behaviors. Particularly, the millennial generation is required to possess digital literacy proficiencies, encompassing the capacity to securely and accurately access, manage, comprehend, integrate, communicate, evaluate, and generate information through digital literacy. Digital literacy has numerous advantages, including the enhancement of one's ability to concentrate and maintain attention. Another advantage for an individual is their capacity to comprehend information, which enhances their aptitude to construct coherent sentences and produce written content. Digital literacy is intricately linked to the preservation of culture. In this context, conservation does not solely pertain to the environment and vegetation, but rather encompasses the endeavor to safeguard, maintain, and utilize it in a manner that is environmentally sustainable. The inquiry pertains to the correlation between digital literacy within the millennial cohort and the preservation of cultural heritage. What is the influence of digital literacy on the comprehension of cultural conservation ideals among the millennial generation? The present study employed a qualitative methodology, specifically utilizing a continuous descriptive approach. Continuity description study involves conducting descriptive research on a specific subject over an extended period of time. The study findings indicate that millennials' comprehension of the significance of cultural preservation through digital literacy is based on three key criteria: civic literacy, global citizenship, and digital citizenship.